As she likes it : Shakespeare's unruly women - Gay, Penny, 1945- (Gender in performance., 1994)
As She Likes It tackles the question of how the unruly women at the centre of Shakespeare's comedies have been embodied in performance. Unique amongst both Shakespearean and feminist studies, As She Likes It asks how gender politics affect the production of the comedies, and how gender is represented, both in the text and on the stage. Penny Gay takes a fascinating look at the way Twelfth Night, The Taming of the Shrew, Much Ado About Nothing, As You Like It and Measure for Measure have been staged over the last half-century, when perceptions of gender roles have undergone massive changes. She also interrogates, rigorously and thoughtfully, the relationship between a male theatrical establishment and a burgeoning feminist approach to performance. As illuminating for practitioners as it will be enjoyable and useful for students, As She Likes It will be critical reading for anyone interested in women's experience of theatre.